2021
DOI: 10.1111/desc.13136
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, but to which environment? Individual differences in sensitivity to parents and peers show domain‐specific patterns and a negative genetic correlation

Abstract: The idea that individuals differ in their sensitivity to the environment's effects is a cornerstone of developmental science. It has been demonstrated repeatedly, for different kinds of stressors, outcomes, and sensitivity markers. However, almost no empirical work was done to examine whether environmental sensitivity is domain-general (i.e., the same individuals are sensitive to different environmental contexts) or domainspecific (i.e., different individuals are sensitive to different environmental contexts),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…The second hypothesis is the domain-specific hypothesis of plasticity factor, which states that in a given environment (e.g., quality of nurture), factor "A" become a plasticity factor, but factor "B" does not. Underpinning the assertion of this hypothesis is the recent finding that there is growing support for the view that susceptibility to positive and negative environmental influences does not function in all environments (i.e., domain-general) but only in specific environments (i.e., domain-specific) (Belsky et al, 2022;Hentges et al, 2023;Markovitch et al, 2023;. The findings and theories that explain these hypotheses may be useful for further understanding individual differences in human developmental plasticity.…”
Section: Discussionmentioning
confidence: 96%
“…The second hypothesis is the domain-specific hypothesis of plasticity factor, which states that in a given environment (e.g., quality of nurture), factor "A" become a plasticity factor, but factor "B" does not. Underpinning the assertion of this hypothesis is the recent finding that there is growing support for the view that susceptibility to positive and negative environmental influences does not function in all environments (i.e., domain-general) but only in specific environments (i.e., domain-specific) (Belsky et al, 2022;Hentges et al, 2023;Markovitch et al, 2023;. The findings and theories that explain these hypotheses may be useful for further understanding individual differences in human developmental plasticity.…”
Section: Discussionmentioning
confidence: 96%
“…However, since each study focused on one or a small number of environmental factors (as well as susceptibility factors), the question of whether sensitive children are generally more sensitive to all environmental input (i.e., domaingenerality) or only to specific environmental input (i.e., domain-specificity) remains open. This important question has been repeatedly raised in the literature (27,34,145) but has not been empirically tested until recently (146)(147)(148)(149). Belsky et al (146) found that different children were sensitive to the different environmental attributes of the childcare effect.…”
Section: Discussionmentioning
confidence: 99%